Comparative Analysis of "A Thousand Splendid Suns" and a Similar Work in Uzbek Literature - Sokhila Aminova (Zien Journals, 2024)
This article presents a comparative analysis of Khaled Hosseini's renowned novel "A Thousand Splendid Suns" and comparable works in Uzbek literature. The analysis explores the similarities and differences between the two literary traditions, examining themes, analytical methods, and cultural influences. Both the novel and Uzbek literature delve into the complexities of women's experiences, the impact of war and political unrest, and the pursuit of personal freedom. The narrative styles in both works employ vivid imagery, emotional depth, and multi-layered storytelling techniques. The comparative analysis highlights the resilience of individuals in the face of hardships, the role of women in traditional societies, and the unique narrative approaches used by the authors. The article concludes by emphasizing the valuable insights offered by these literary works and the need for further exploration and analysis of diverse voices in literature.
Keywords: Comparative analysis; A Thousand Splendid Sun, similarities; difference; traditions